Charge self-consistent dynamical mean-field theory based on the full-potential linear muffin-tin orbital method: Methodology and applications - Grånäs, O.; Di Marco, I.; Thunström, P.; Nordström, L.; Eriksson, O.; Björkman, T.; Wills, J.M. (Computational materials science, 2012)
► We implemented the charge self-consistent LDA+DMFT scheme into a FP-LMTO method. ► The description of bcc Fe in our method is improved with respect to standard DFT–LDA. ► The physical properties of SmCo5 are very well described in our method. ► Charge self-consistence is not important for bcc Fe but is necessary for SmCo5. Full charge self-consistence (CSC) over the electron density has been implemented into the local density approximation plus dynamical mean-field theory (LDA+DMFT) scheme based on a full-potential linear muffin-tin orbital method (FP-LMTO). Computational details on the construction of the electron density from the density matrix are provided. The method is tested on the prototypical charge-transfer insulator NiO using a simple static Hartree–Fock approximation as impurity solver. The spectral and ground state properties of bcc Fe are then addressed, by means of the spin-polarized T-matrix fluctuation exchange solver (SPTF). Finally the permanent magnet SmCo5 is studied using multiple impurity solvers, SPTF and Hubbard I, as the strength of the local Coulomb interaction on the Sm and Co sites are drastically different. The developed CSC–DMFT method is shown to in general improve on materials properties like magnetic moments, electronic structure and the materials density.